Intra-articular Osteoid Osteoma of the Elbow: A Report of 10 Cases Treated With Open Surgery - Farid Najdmazhar; Hooman Shariatzadeh; Hosein Hamadiyan; Ahamad Ibrahim Hasasn; Abdorrasoul Layeghi (Advanced Biomedical Research)
Background: Intra-articular osteoid osteoma of the elbow is very rare,‏ and diagnosis is challenging. Materials and Methods: Ten patients with intra-articular osteoid osteoma of the elbow were treated with open surgery. Outcomes and postoperative surgical complications were evaluated. Results: The mean age of the patients was 20.9 ± 6.9 years. Before surgery, VAS for elbow pain was 5.4 ± 0.51. None of the patients had pain in the last follow-up (P < 0.001). Elbow ROM was 89 ± 32° before the operation and 130 ± 14° in the follow-up (P < 0.001). MEPS of the patients was 63.5 ± 7.8% before the operation and 97.5 ± 3.5 in the follow-up (P < 0.001). Three patients had limited elbow ROM in the last follow-up (range 15-35°). No local recurrence was recorded at a mean follow-up of 4.9 ± 2.8 years. Conclusion: Considering the small rate of postoperative complications and no local recurrence, open surgical resection could be regarded as a safe and efficient treatment for intra-articular osteoid osteoma of the elbow.